2010
DOI: 10.1097/mot.0b013e3283387f75
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia and outcome after partial hepatectomy for adult-to-adult donor transplantation

Abstract: Live liver donation is a valuable option for organ donation that can be conducted safely with a multidisciplinary perioperative approach. Future considerations should focus on the recovery period and how the intraoperative management can be optimized to minimize the impact of surgery on donors' quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 56 publications
1
29
0
1
Order By: Relevance
“…Living-donor liver transplantation is increasingly being used as an effective treatment for patients with endstage liver disease [1]. Any strategy to reduce blood loss during hepatectomy is important and various surgical [2,3] and anaesthetic [4][5][6] methods have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Living-donor liver transplantation is increasingly being used as an effective treatment for patients with endstage liver disease [1]. Any strategy to reduce blood loss during hepatectomy is important and various surgical [2,3] and anaesthetic [4][5][6] methods have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Hwang ve ark. (5) , tarafından ameliyat sonrası donörlerin en az 3 ay hem fiziksel hem de psikolojik yönden olumsuz etkilendikleri ve bunun yaşam kalitelerini olumsuz etkileyebildiği bildirilmiştir. Bundan dolayı karaciğer vericilerinde postoperatif ağrının etkili ve güvenli bir şekilde yönetilmesi gerekmektedir.…”
Section: Bulgularunclassified
“…Despite the absence of definitive data about adverse outcome, since hydroxyethyl starch solutions are known to effect the coagulation system, they should be used with caution. 5% albumin can be used after hepatectomy, but it has also no proven benefit (Hwang and McCluskey, 2010).…”
Section: Anesthetic Management Of the Living Donorsmentioning
confidence: 99%
“…Hwang and McCluskey reported that intravenous patient-controlled analgesia or intrathecal morphine may become an alternative for pain control in living donors. Regional techniques such as paraspinal blocks, transversus abdominus plane blocks, incisional field blocks are still investigated for their effect and safety in these patients (Hwang and McCluskey, 2010).…”
Section: Anesthetic Management Of the Living Donorsmentioning
confidence: 99%
See 1 more Smart Citation